DIAGNOSTICS AND TREATMENT OF PERFORATED PYLORODUODENUM ULCERS IN WOMEN - A. G. Khasanov; M. B. Galin; F. F. Badretdinova; M. A. Nurtdinov; R. Kh. Shaikhinurov (Вестник хирургии имени И.И. Грекова, 2016)
The results of treatment of 75 women with perforated ulcers have been studied. There were prevailed women of middle and elderly age groups among patients who underwent surgery. A wound closure of perforated opening and abdominal sanation were performed by laparoscopic means in 30,7% of patients and using midline laparotomy in 29,3% cases. There were carried out the laparoscopic sanation of the abdominal cavity and the wound closure of perforated ulcer from mini-access using the set of mini-assistant in 10,7% patients. Radical operations were applied in 16% cases. The early postoperative complications took place in 8,1% of the patients, the rate of lethality was 4,0%. The long-term results were evaluated and considered as good in 55,5% women, satisfactory - in 30,1% and unsatisfactory - in 14,2% cases.